Belgium : Detailed Assessment of Compliance with the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2013)
The Belgian financial system is relatively large, concentrated, and interconnected and has a high level of compliance with the Basel Core Principles (BCPs) for effective banking supervision. The National Bank of Belgium (NBB) deploys high-quality supervisory practices and has clear lines of accountability, transparency, and separate funding when acting in its supervisory capacity. The Belgian authorities have established a Resolution Fund (RF) vesting it with powers to take preventative measures and to facilitate resolution procedures.